Addressing barriers to the use of value capture to fund transit-oriented developments. Issue 2 (June 2021) - Mathur, Shishir; Gatdula, Aaron
Highlights: Most of the transit agencies are not allowed to purchase land for constructing TODs. Most of the transit agencies do not have land use and zoning powers over the station-area land. Local governments rarely use of power eminent domain to assemble land parcels to enable TODs. Land use, zoning, and value capture needs to be considered in an integrated manner. More power should be granted to transit agencies over station-area land.